FORMING TEACHER COMMITMENTS IN THE STATE ISLAMIC JUNIOR HIGH SCHOOL (MTs) OF MEDAN CITY (Study of the Effects of Leadership, Work Team and Decision Making on Work Commitments of The teachers of State Islamic Junior High School (MTs) of Medan City) - Muhammad Rifai Rifai (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2019)
This study aims to determine: (1) The effect of leadership on the work commitments of teachers of State Islamic Junior High School of Medan City, (2) The influence of work teams on the work commitments of Teachers of State Islamic Junior High School of Medan City, (3) The effect of decision making on the work commitments of Teachers of State Islamic Junior High School of Medan City. The research method is path analysis which aims to obtain the influence of exogenous variables on endogenous variables of research. The subjects of the study were Teachers of State Islamic Junior High School of Medan City. With a total sample of 155 people. Sampling was carried out using proportional random sampling techniques. The path analysis research method aims to test the theory and obtain information about the research. Based on hypothesis testing it can be concluded: (1) there is an influence of leadership on teacher work commitments (2) there is an influence of work teams on teacher work commitments (3) there is an influence of decision making on teacher work commitments. These three variables have an impact on the formation of teacher work commitments of 48.5%. Efforts to establish teacher work commitments are determinants in educational institutions. Teachers who have a strong commitment to work and the institution will make it work more professionally and without pressure. For this reason, systematic and sustainable efforts are needed to form teacher work commitments. Keywords: Leadership, Team Work, Decision making, Teachers’ Work Commitment